ANALYSIS OF COLLECTIVE ACTION THEORY IN DEVELOPMENT PHENOMENON SEA FENCE IN INDONESIA - PANDI FIRMAN; WIWIN SEPTIADI; IRWAN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
Fence construction the sea in Indonesia is one of effort collective in face impact change climate and abrasion beach. Phenomenon This can analyzed use theory Collective Action in analyze individuals and groups Work The same For reach objective together in management source Power common - pool resources Research This aiming analyze dynamics Collective Action in development fence sea in Indonesia and the challenges and strategies in implementation. Research This use approach qualitative with type study descriptive with method data collection namely study library and study Documents. Data management using Milles and Huberman's thoughts which began with data collection, data reduction, data presentation and drawing conclusions. Research results This show that success Collective Action in development fence sea determined by the strength of social capital, trust inter-factor, existence regulation government and incentives economy for public local. The challenges faced are limited resources, weak coordination and differences in interests between stakeholders. Therefore, a more adaptive and collaborative strategy is needed to increase the effectiveness of Collective Action in the management and construction of sustainable sea fences.